Students' Onto-Semiotic Approach in Solving Mathematics Problems - Wibowo, Teguh; Susianti, Elena; Purwoko, Riawan Yudi (Jurnal Riset Pendidikan Matematika, 2024)
This study aims to identify and analyze the stages of students' onto-semiotic approach to solving mathematical problems. This research is based on the mathematical object of the onto-semiotic approach, namely language, concepts, propositions, procedures, situations, and arguments. This research is qualitative research with a phenomenological type. The research subjects were high school students of eleventh grade. The technique of taking the subject is using a purposeful sampling technique. The research instrument used a test in the form of a linear program description question. The results of the study show that the onto-semiotic approach contains language stages including changing contextual objects into variables, writing mathematical symbols, writing mathematical models, and others; the concept stage includes students creating and filling in tables by grouping the objects in the problem to make it easier to solve mathematical problems; the proposition stage consists of the reasons students cannot replace variables; the procedure stage include simplifying coefficients and constants, how to get the value of each variable, and others; the situation stage includes writing a mathematical model that will be used to find the value of each variable, find the point of intersection of the line, and others.